A Vanillinyl‐Hydrazone Schiff Base: Recognition of Mg2+, Zn2+, Cd2+ and I− by Turn‐On Fluorescence Method. Issue 27 (20th July 2020) - Dey, Sunanda; Purkait, Rakesh; Mallick, Debashis; Sinha, Chittaranjan
Abstract: Vanillinyl‐hydrazone Schiff base, 2, 6‐Bis‐[(2‐hydroxy‐3‐methoxy‐benzylidene)‐hydrazonomethyl]‐4‐methyl‐phenol (PHV) is characterized by spectroscopic techniques and serves as selective and sensitive fluorescence sensor at different emission wavelength for Zn 2+ (λem, 546 nm), Cd 2+ (λem, 567 nm) and Mg 2+ (λem, 625 nm) in DMSO/H2 O medium (9 : 1, v/v) in presence of large number of available cations. The probe also displays selective turn‐on fluorescence sensitivity to I − (λem, 635 nm) in THF medium. Density Functional Theory (DFT) computation techniques are used to explain some of the obtained experimental observation. Abstract : A new Vanillinyl‐hydrazone Schiff base (PHV ), characterised by 1 H NMR, ESI‐MS and FTIR, serves fluorescence sensitivity at different emission wavelength for Zn 2+ (λem, 546 nm), Cd 2+ (λem, 567 nm), Mg 2+ (λem, 625 nm) in DMSO/H2 O medium (9 : 1, v/v) and also displays selective turn‐on fluorescence sensitivity to I − (λem, 635 nm) in THF medium. The binding composition is supported by Job's plot. To correlate between the experimental findings and theoretical calculation, Density Functional Theory (DFT) computation techniques are used.